Phenomenological retrieval style of autobiographical memories in a sample of major depressed individuals - Lolich, María (2017)
Autobiographical memory retrieval implies different phenomenological features. Given the lack of previous work in Hispanic-speaking populations, 34 in depth interview were carried out in individuals with and without Major Depressive Disorder in Buenos Aires, Argentina. Phenomenological components during the evocation of autobiographical memories were explored. Data was qualitatively analyzed using Grounded Theory. During the descriptive analyses, seven phenomenological categories were detected as emerging from the discourse. The axial and selective analyses revealed two main discursive axles areas; rhetoric-propo sitional and specificity- generalized. The impact on affective regulation processes, derived from the assumption of an amodal or multimodal style of processing autobiographical infor mation, merits further attention.